1994
DOI: 10.1002/joc.3370140604
|View full text |Cite
|
Sign up to set email alerts
|

Recent and future climate change in east asia

Abstract: The signing of the UN Framework Convention on Climate Change in Rio de Janeiro in June 1992 by 160 nations has firmly identified global climate change due to human pollution as a pressing global environmental concern. Among the responsibilities that the nations which ratify the Convention will have are the drawing up of inventories of greenhouse gas sourccs and sinks and the formulation of national strategies to respond to climate change through adaptive and/or preventive measures. One requirement for identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 33 publications
5
61
1
5
Order By: Relevance
“…Our reconstruction agrees well with the East Asia MAM temperature curve of Hulme et al (1994), with the exceptions of variations during the 1960s and 1980s, when our reconstructed temperatures appear lower than the instrumental record. In addition, our record does not record the century-length trend in instrumental temperature, which culminates in extreme warmth during the 1980s (Hulme et al 1994 [their Figure 3]; Yatagai and Yasunari, 1994 [their Figure 4]).…”
Section: Comparisons With Other Evidencesupporting
confidence: 81%
See 1 more Smart Citation
“…Our reconstruction agrees well with the East Asia MAM temperature curve of Hulme et al (1994), with the exceptions of variations during the 1960s and 1980s, when our reconstructed temperatures appear lower than the instrumental record. In addition, our record does not record the century-length trend in instrumental temperature, which culminates in extreme warmth during the 1980s (Hulme et al 1994 [their Figure 3]; Yatagai and Yasunari, 1994 [their Figure 4]).…”
Section: Comparisons With Other Evidencesupporting
confidence: 81%
“…Warm springs (March through May; MAM) during the aforementioned periods are noted by instrumental mean temperature records for East Asia, which, prior to 1950, rely heavily on the long records of coastal stations (Hulme et al 1994). Our reconstruction agrees well with the East Asia MAM temperature curve of Hulme et al (1994), with the exceptions of variations during the 1960s and 1980s, when our reconstructed temperatures appear lower than the instrumental record.…”
Section: Comparisons With Other Evidencesupporting
confidence: 69%
“…Over eastern Asia, the modeling of regional scale precipitation sensitivity to global warming also has many uncertainties (Li et al 1994(Li et al , 1995. For example, in earlier GCM experiments presented by Hulme et al (1994), precipitation was estimated to rise over most of eastern Asia in all seasons; however, the uncertainty range attached to this estimate is much wider. It is hard to tell whether the recently observed wetter trend has been induced by the enhanced greenhouse effect.…”
Section: Mostmentioning
confidence: 94%
“…However, the EAM change under global warming conditions has hardly been investigated. Wang & Ye (1993) and Nitta & Hu (1996) found from observational data a pronounced warming trend in North China.Using observational data, Hulme et al (1994) concluded that coinciding with warming in the last century, East Asian precipitation increased with a trend of 0.54% decade -1 , which is larger than the global average for land areas (0.25% decade -1 ). Analyzing model simulations, they further suggested that by 2050 the mean temperatures of East Asia will be higher than the warm seasonal anomalies that occurred during the last decade.…”
mentioning
confidence: 99%